Randomized trial evaluating self-sampling for HPV DNA based tests for cervical cancer screening in Nigeria. Issue 1 (December 2017) - Modibbo, Fatima; Iregbu, K.; Okuma, James; Leeman, Annemiek; Kasius, Annemieke; de Koning, Maurits; Quint, Wim; Adebamowo, Clement
Abstract Background Cervical cancer incidence and mortality rates in Sub-Saharan Africa (SSA) remain high due to several factors including low levels of uptake of cervical cancer screening. Self-collection of cervicovaginal samples for HPV DNA testing may be an effective modality that can increase uptake of cervical cancer screening in SSA and hard to reach populations in developed countries. We investigated whether self-collection of cervicovaginal samples for HPV DNA tests would be associated with increased uptake of screening compared with clinic based collection of samples. Furthermore, we compared the quality of samples collected by both approaches for use in HPV genotyping. Methods We conducted a community based randomized trial in a semi-urban district of Abuja, Nigeria with 400 women, aged 30 to 65 years randomized to either hospital-collection or self-collection of cervicovaginal samples. We compared cervical cancer screening uptake among the 2 groups and evaluated the concentration of human DNA in the samples by measuring RNase P gene levels using qPCR. High-risk HPV DNA detection and typing was done using the GP5+/6+ Luminex system. Results Most participants in the self-collection arm (93%, 185/200) submitted their samples while only 56% (113/200) of those invited to the hospital for sample collection attended and were screened during the study period (p value < 0.001). Human genomic DNA was detected in all but five (1.7%) participants, all of whom were in the self-collection arm. The prevalence of high-risk HPV in the study population was 10% with types 35, 52 and 18 being the commonest. Conclusions Our study shows that self-sampling significantly increased uptake of HPV DNA based test for cervical cancer screening in this population and the samples collected were adequate for HPV detection and genotyping. Cervical cancer screening programs that incorporate self-sampling and HPV DNA tests are feasible and may significantly improve uptake of cervical cancer screening in SSA.